Fe3O4 loaded on ball milling biochar enhanced bisphenol a removal by activating persulfate: Performance and activating mechanism. (1st October 2022) - Yu, Yunjiang; Guo, Haobo; Zhong, Zijuan; Wang, Anqi; Xiang, Mingdeng; Xu, Senhao; Dong, Chenyin; Chang, Zhaofeng
Abstract: In this study, pristine biochar (BC), ball milling biochar (MBC), Fe3 O4 modified BC (Fe3 O4 @BC), and Fe3 O4 modified MBC (Fe3 O4 @MBC) were prepared to compare the Bisphenol A (BPA) removal efficiency by activating persulfate (PDS). All catalysts exhibited excellent degradation rather than adsorption in the PDS system, and Fe3 O4 @MBC800 had the best BPA removal efficiency, with 96.73% degradation and negligible 1.43% adsorption due to the synergistic effect between MBC800 and Fe3 O4 particles. Radical quenching experiments and electron paramagnetic resonance analysis indicated radical pathways, namely, SO4 ∙ - and ∙OH, O2 ∙ -, and non-radical pathway ( 1 O2 ) involving BPA degradation. The abundant oxygen-containing groups, increased graphitization and mesopores of MBC800, and Fe 3+ /Fe 2+ conversion of Fe3 O4 particles facilitated PDS activation to produce reactive oxygen species. In addition, the superior electrochemical performance accelerated the electron transfer between the catalyst and PDS, promoting BPA degradation in the Fe3 O4 @MBC800/PDS system. More importantly, Fe3 O4 @MBC800 is resistant to environmental interference, including pH, anions, cations, and humic acid, and has good catalytic reusability and stability, which fulfills the requirements of engineering applications. Therefore, Fe3 O4 loaded on ball-milled biochar provides a convenient strategy for preparing environmentally friendly, economical, and efficient carbon-based catalysts to remove organic contaminants. Graphical abstract: Image 1 Highlights: Fe3 O4 modified ball-milled biochar (MBC) had the best surface properties. Fe3 O4 modified 800 °C-MBC (Fe3 O4 @MBC800) showed the highest BPA removal efficiency. SO4 ∙ -, ∙OH and O2 ∙ -, and non-radical pathway ( 1 O2 ) are involved in BPA degradation. Synergistic effect between MBC800 and Fe3 O4 facilitate persulfate activation. Fe3 O4 @MBC800 is reusable, stable and resistant to environmental interference.